2011
DOI: 10.3892/ol.2011.457
|View full text |Cite
|
Sign up to set email alerts
|

A case of long-term survival of metastatic desmoplastic small round cell tumor treated with multimodal therapy

Abstract: Abstract. Desmoplastic small round cell tumor (DSRCT) is a rare, aggressive and malignant tumor that predominantly affects young males. No standard therapy is currently available for patients with DSRCT and the prognosis remains extremely poor. In this study, we report a thought-provoking DSRCT case. A 24-year-old male was admitted to our hospital with a chief complaint of hematemesis. Computed tomography revealed a retrovesical mass with a splenic hilar tumor, multiple lung and liver tumors and marked lymph n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…ifosfamide based regimens, n = 5, API, n = 1; or other (cyclophosphamide based or etoposidecisplatin, n = 5), for a median of 4 cycles (range 3-10 cycles). 22,23 Partial radiologic response and stable disease were observed in 68 and 23 % of the patients, respectively. There was no complete radiologic response.…”
Section: Chemotherapymentioning
confidence: 96%
“…ifosfamide based regimens, n = 5, API, n = 1; or other (cyclophosphamide based or etoposidecisplatin, n = 5), for a median of 4 cycles (range 3-10 cycles). 22,23 Partial radiologic response and stable disease were observed in 68 and 23 % of the patients, respectively. There was no complete radiologic response.…”
Section: Chemotherapymentioning
confidence: 96%
“…A modified P6 regimen and a modified PAVEP regimen [ 63 , 68 ] (cyclophosphamide, pirarubicin, etoposide, and cisplatin) have been employed to decrease severe adverse events and to improve the completion rate of chemotherapy. These modified regimens use Cytoxan of 4 g/m 2 and replace Adriamycin with pirarubicin.…”
Section: Treatmentmentioning
confidence: 99%
“…A clinical report of 20 abdominal DSRCT cases showed that the median overall survival (OS) was 22 months (interquartile range: 12–28 months), and that the 5‐year OS rate was 20% . However, cases of long‐term survival of metastatic DSRCT have recently been reported . Here we present two autopsy cases of DSRCT, that is, an aggressive case (survival after initial symptoms was only 12 months) and a long‐term survival case (survival after primary hospitalization was 42 months).…”
Section: Introductionmentioning
confidence: 88%
“…5 However, cases of long-term survival of metastatic DSRCT have recently been reported. 6 Here we present two autopsy cases of DSRCT, that is, an aggressive case (survival after initial symptoms was only 12 months) and a long-term survival case (survival after primary hospitalization was 42 months). Table 1 shows the clinical summary of both cases including patient characteristics, clinical and imaging findings, initial diagnosis (clinical/histological), treatments, and outcomes.…”
Section: Introductionmentioning
confidence: 99%